Middle school students’ psychological health on suicide ideation: based on latent profile analysis - Wei, Meiting; Liu, Jiang (Frontiers in Public Health, 2024)
Introduction: This study identifies potential categories of mental health for adolescents in different school years and further analyzes the relationship between these categories and suicidal ideation.Methods: A total of 1944 middle school students completed SCL-90 and Self-rating Idea of Suicide Scale on November 29, 2022, selecting via a whole-group sampling method. Latent profile analysis was used to analyze the psychological health subtypes of students from a middle school in Southwest China. The R3step method and the DU3step method were conducted to analyze the predictive role of demographic variables and the effects of different profiles on suicidal ideation.Results: Different potential categories of psychological health were observed among middle school students. Junior middle school students can be classified into three types: Psychological Health Type (62.3%), Low-risk Type (27.1%) and High-risk Type (10.7%). Senior middle school students can be classified into four types: Psychological Health Type (43.3%), Low-risk Type (33.9%), Medium -risk Type (16.8%), and High-risk Type (6.0%). Gender and subjective family atmosphere are predictors of psychological health, and they also influence the population distribution of psychological health patterns in different sections of middle school students. Girls and students with poor subjective family atmosphere are more prone to experiencing psychological problems. There were significant differences in suicidal ideation among different potential categories of psychological health of different sections middle school students ( 2 =1178.71, 1174.85, p＜0.001). Among senior high school students classified as High-risk Type, they exhibitedhave the highest score for suicidal ideation.Conclusions: There is obvious group heterogeneity in psychological health of different sections middle school students. Older students are more likely to have suicidal thoughts.